Dose-Response and Time-Course of a-Tocoferol Mediating the Cytoprotection Of Dental Pulp Cells Against Hydrogen Peroxide - Vargas, Fernanda Da Silveira; Soares, Diana Gabriela; Basso, Fernanda Gonçalves; Hebling, Josimeri; Costa, Carlos Alberto De Souza (Fundação Odontológica de Ribeirão Preto, 2014)
This in vitro study evaluated the potential protective effect of vitamin E alpha-tocopherol (α-T) isomer against the toxicity of hydrogen peroxide (HP) applied on dental pulp cells. Odontoblast-like MDPC-23 cells were seeded on 96-well plates for 72 h, treated with different concentrations of α-T (1, 3, 5, and 10 mM) for different times (1, 4, 8, and 24 h) and then exposed or not to a 0.018% HP solution for 30 min. In positive and negative control groups, cells were exposed to HP or culture medium (DMEM containing 5% DMSO), respectively. Cell viability was assessed by the MTT assay and the absorbance numeric data, expressed as percentage values, were subjected to the statistical analysis by Kruskal-Wallis and Mann-Whitney tests (α=5%). Considering the cells in the negative control as having 100% of cell viability, all combinations of α-T concentrations and pretreatment times showed a protective effect against HP cytotoxicity. Significant reduction of cell viability (59%) was observed in the positive control compared with the negative control. The highest values of pulp cell viability were obtained after pretreatment with 1 and 3 mM α-T concentrations for 24 h followed by exposure to HP (126% and 97% of cell viability, respectively). Under the tested conditions, the most effective cell protection against the cytotoxic effects of HP was provided by the lowest concentrations of α-T (1 and 3 mM) applied for 24 h.

Neste estudo, foi avaliado o potencial protetor do isômero alfa-tocoferol da vitamina E (-T) contra a ação tóxica do peróxido de hidrogênio (PH) aplicado sobre células pulpares. Células odontoblastóides MDPC-23 foram semeadas em placas de 96 compartimentos por 72 h, tratadas com diferentes concentrações de α-T (1, 3, 5 e 10 mM) por diferentes períodos (1, 4, 8 e 24 h) e, então, expostas ou não a uma solução com 0,0018% de PH por 30 min. Nos controles positivo e negativo, as células foram expostas ao PH ou meio de cultura (DMEM contendo 5% de DMSO), respectivamente. A viabilidade celular foi avaliada pelo teste do MTT e os valores numéricos de absorbância, expressos em porcentagem, foram submetidos a análise estatística pelos testes de Kruskal-Wallis e Mann-Whitney (α=5%). Considerando as células do grupo controle negativo como apresentando 100% de viabilidade celular, todas as combinações de α-T, nas diferentes concentrações, e tempos de pré-tratamento demonstraram um efeito protetor contra a citotoxicidade do PH. Redução significativa da viabilidade (59%) foi observada para o grupo controle positivo comparado ao controle negativo. Os maiores valores de viabilidade celular foram obtidos após pré-tratamento com 1 e 3 mM de α-T por 24 h seguido de exposição ao PH (126% e 97% de viabilidade celular, respectivamente). Assim, de acordo com as condições experimentais, o efeito protetor mais efetivo contra os efeitos tóxicos do PH foi observado para as menores concentrações de α-T (1 e 3 mM) aplicado por 24 h.
Keywords: hydrogen peroxide; odontoblasts; tooth bleaching; vitamin E.